Association between private and public places and practice of physical activity in adults - Priscila Missaki Nakamura; Inaian Pignatti Teixeira; Adriano Akira F Hino; Jacqueline Kerr; Eduardo Kokubun (Universidade Federal de Santa Catarina, 2016)
There are some studies that showed the relationship between built environment with practice of physical activity during leisure-time and active transportation in the adult population. However, this relationship may be influence by type and intensity of physical activity. The aim of this study was to verify association between public and private places for engaging in different types of physical activity in adults of Rio Claro City, Brazil. Cross sectional study with representative sample of 1588 adults with a mean age of 45.7±17.0 years completed the IPAQ-long form. Geographic Information System data were employed to assess the built environment. The time to different physical activity types were divided in actives (≥10 min/week) and inactive (<10 min/week). Poisson Multilevel Regression Analysis was performed in the Stata version 12.0. After adjusting for confounders, walking during leisure-time was positively associated with São Paulo's Social Vulnerability Index (SSVI) categories of 1 (PR=2.77) through 5 (PR=1.94) and negatively associated with population density higher than 68 km/m2 (PR=0.70). Vigorous intensity physical activity was negatively associated with distance greater than 596 metes of private places to practice physical activity (PR=0.50). Total leisure time physical activity was positively associated with SSVI 1 (PR=2.48) and 5 (RP=1.89). Moderate intensity physical activity was not associated with built environment factors. There were differents associations between the built environment factors with leisure time PA except to moderate intensity physical activity.